Carcinoid transformation of presacral dermoid cyst in patient with currarino syndrome: a case report. (4th May 2019) - Colombo, Francesca; Janous, Petr; Buxton, Neil
Abstract: Currarino syndrome (CS) is a congenital disorder characterized by partial sacral agenesis, anorectal malformation and a presacral mass. Only three cases of carcinoid transformation of the presacral mass have been described in the literature. We present a case of carcinoid transformation of presacral dermoid cyst in patient with Currarino syndrome.